Kenya : 2011 Article IV Consultation, Second Review Under the Three-Year Arrangement Under the Extended Credit Facility and Requests for Modification of Performance Criteria and Augmentation of Access: Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Kenya. (IMF Staff Country Reports; Country Report ;, 2012)
This paper discusses key findings of the Second Review for Kenya under the Extended Credit Facility (ECF). Program implementation during the first half of 2011 was in line with the objectives. All quantitative performance criteria and indicative targets for June 2011 have been met. The authorities have requested augmentation of access under the ECF arrangement to deal with the impact of the drought and higher-than-anticipated international prices. They have adopted additional measures to address macroeconomic imbalances.